CORRELATION BETWEEN MALARIA AND ANEMIA: A LITERATURE REVIEW - Pratiwi, Dian; Tosepu, Ramadhan (Universitas Halu Oleo, 2024)
ABSTRACT Malaria and anemia are the main underlying factors for illness in children. Malaria is a cause of death and illness, especially in children under 5 years of age. A total of 214 million populations affected by clinical malaria were reported in 2018 and caused 438,000 deaths, most of them are children in Africa.The purpose of this study was to assess the association between malaria and anemia in children. This study uses a literature review approach regarding research Google and Google Scholar are used as the main source of databases accessed on October 09, 2023 to extract research published in English that addresses the foreign context. With keywords combination: